Ulnar Neuropathy at the Elbow Associated With Focal Demyelination in the Proximal Forearm and Intraoperative Imaging Correlation - Abuzinadah, Ahmad R.; Addas, Bassam M. J. (Frontiers in Neurology, 2019)
Ulnar nerve focal demyelination (FD) in the forearm [defined as conduction block (CB) and or temporal dispersion (TD)] has been described with immune-mediated neuropathy and with compression affecting the forearm segment of the nerve. The association of FD in the forearm with entrapment ulnar neuropathy at the elbow, as well as the intraoperative imaging of the abnormal ulnar nerve at the flexor carpi ulnaris muscle level (FCU), has not been reported before. We report a 33-year-old woman presented with only sensory symptoms of the right hand suggestive of right ulnar neuropathy for the last ten years. On clinical examination, she had reduced pinprick sensation on the little and ring fingers with no motor deficit. Nerve-conduction study showed slowing of conduction velocity across the elbow on the right when recording at the abductor digiti minimi (ADM) and first dorsal interossei (FDI). There was 63% amplitude drop when stimulating below the elbow compared to distal stimulation at the wrist. Increment inching study localized the block at 5 cm distal to the medial epicondyle. During surgical transposition, the ulnar nerve was swollen, and edematous in the segment where the nerve enters the FCU muscle, which provides a physiological explanation for the electrophysiological findings. After the surgery, the patient reported complete resolution of the symptoms. This case demonstrate that ulnar nerve motor potential FD at the proximal forearm could be recorded and it is still compatible with ulnar-nerve entrapment at the elbow.